Complementary feeding practices and associated factors of dietary diversity among uncomplicated severe acute malnourished children aged 6–23 months in Burkina Faso. Issue 4 (1st June 2021) - Nikièma, Victor; Fogny, Nadia F.; Salpéteur, Cécile; Lachat, Carl; Kangas, Suvi T.
Abstract: Nutritional treatment of children with uncomplicated severe acute malnutrition (SAM) is based on ready‐to‐use therapeutic foods (RUTF). With treatment provided at community level, children could have access to other foods, and a reduction in the dose of RUTF could further increase dietary diversity during treatment. We assessed the dietary diversity score (DDS), the minimum dietary diversity (MDD), the minimum meal frequency (MMF) and the minimum acceptable diet (MAD) of 459 infants and young children aged 6–23 months being treated for SAM with different doses of RUTF. We also investigated the factors associated with DDS. Dietary intake was estimated using a single 24‐h multipass dietary recall, 1 month after starting treatment, from December 2016 to August 2018. The DDS was calculated on the basis of eight food groups. Differences between children receiving the reduced RUTF and the standard RUTF dose and factors associated with DDS were assessed by Poisson and logistic regression models. RUTF dose was not associated with DDS (4.07 ± 1.25 for reduced RUTF and 4.01 ± 1.26 for standard RUTF; P  = 0.77). Food groups most consumed by children were grains, roots or tubers (96%) and legumes and nuts (72%). Eggs consumption was low (3%). DDS was positively associated with child's age, mother's education, household wealth index, urban residence and rainy season. The present findings show that children with SAM consumed a variety of foods during treatment in addition to the RUTF ration prescribed to them. Reducing the dose of RUTF during SAM treatment did not impact DDS.